2018
DOI: 10.3389/fevo.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Wasps Can Reduce Mortality of Teosinte Plants Infested With Fall Armyworm: Support for a Defensive Function of Herbivore-Induced Plant Volatiles

Abstract: Many parasitic wasps use volatiles emitted by plants under herbivore attack to find their hosts. It has therefore been proposed that these inducible plant volatiles serve an indirect defense function by recruiting parasitoids and other natural enemies. This suggested function remains controversial because there is little evidence that, in terms of fitness, plants benefit from the actions of natural enemies, particularly parasitoids, which do not immediately kill their hosts. We aimed to address this controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Maize plants of 10 to 21 days old (3-9 leaf stages) emit induced volatiles when Spodoptera exigua or S. littoralis feed on the young leaves and consequently attract more natural enemies compared to undamaged plants (D'Alessandro et al 2009;Turlings et al 1991;Fritzsche-Hoballah and Turlings 2001). While most studies on HIPVs and natural enemies have been conducted under controlled laboratory conditions, some have demonstrated their effects under field environments (Aartsma et al 2019(Aartsma et al , 2020Bernasconi Ockroy et al 2001;De Lange et al 2018;Drukker et al 1995;Poelman et al 2009;Shimoda et al 1997). Furthermore, a recent study using 3-leaves stage (9-12 days old) maize plants confirmed that S. frugiperda has lower HIPVs induction on maize than other Spodoptera species (De Lange et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Maize plants of 10 to 21 days old (3-9 leaf stages) emit induced volatiles when Spodoptera exigua or S. littoralis feed on the young leaves and consequently attract more natural enemies compared to undamaged plants (D'Alessandro et al 2009;Turlings et al 1991;Fritzsche-Hoballah and Turlings 2001). While most studies on HIPVs and natural enemies have been conducted under controlled laboratory conditions, some have demonstrated their effects under field environments (Aartsma et al 2019(Aartsma et al , 2020Bernasconi Ockroy et al 2001;De Lange et al 2018;Drukker et al 1995;Poelman et al 2009;Shimoda et al 1997). Furthermore, a recent study using 3-leaves stage (9-12 days old) maize plants confirmed that S. frugiperda has lower HIPVs induction on maize than other Spodoptera species (De Lange et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of “field” experiments that demonstrate changes in parasitoid attack rates are small-scale and typically lack adequate controls. Invariably the design consists of a single field into which “test” plants are placed to assess parasitism, usually with both treatments juxtaposed ( Lou et al, 2005 , 2006 ; de Lange et al, 2018 ). Apart from the issues of pseudoreplication associated with such an approach, the key problem is that any change in parasitism rate reflects either a change in parasitoid searching efficiency or a change in number of parasitoids foraging due to a combination of short (within field) or longer-range attraction.…”
Section: Parasitoid Responses To Herbivore Induced Plant Volatilesmentioning
confidence: 99%
“…In addition, it has been proposed that plants protect themselves indirectly by attracting natural enemies of their herbivores with herbivore-induced plant volatiles (HIPVs) (Dicke et al, 2002;Turlings and Wäckers 2004). The function of HIPVs remains topic of discussion (De Lange et al 2018;Dicke and Baldwin, 2010;Hare, 2011;Heil 2014;Poelman 2015;Turlings and Erb, 2018), but various studies have shown that they are highly attractive to predators and parasitoids of the herbivores (e.g. De Moraes et al 1998;Dicke and Sabelis, 1988;Kessler and Baldwin 2001;Thaler 1999;Turlings et al 1990).…”
Section: Introductionmentioning
confidence: 99%